Birth and Death: Studying Ritual, Embodied Practices and Spirituality at the Start and End of Life - Wojtkowiak, Joanna; Mathijssen, Brenda (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Birth and death are both profound life transitions, revealing deeply existential, social, and spiritual questions in addition to various forms of ritual and ritualizing. While birth and death are often seen as opposites, this edited volume shows that the start and end of life share many ambiguities. They represent a beginning and an end, and lead to ritualizing as well as embodied forms of spirituality. Throughout the book, the authors discuss theoretical and empirical perspectives on rituals at birth and death from multidisciplinary perspectives, such as religious studies, anthropology, philosophy, and sociology. By doing so, they shed light on new forms of ritualizing, as well as on traditional rituals.